Recalibration of the lunar chronology due to spatial cratering-rate variability - Lagain, Anthony; Devillepoix, Hadrien; Vernazza, P.; Robertson, D.; Granvik, M.; Pokorny, P.; Ozerov, A.; Shober, P.M.; Jorda, L.; Servis, K.; Fairweather, John; Quesnel, Y.; et al. (2024)
Cratering chronologies are used to derive the history of planetary bodies and assume an isotropic flux of impactors over the entire surface of the Moon. The impactor population is largely dominated by near-Earth-objects (NEOs) since ∼3.5 billion years ago. However, lunar impact probabilities from the currently known NEO population show an excess of impacts close to the poles compared to the equator as well as a latitudinal dependency of the approach angle of impactors. This is accompanied by a variation of the impact flux and speed with the distance from the apex due to the synchronicity of the lunar orbit around the Earth. Here, we compute the spatial dependency of the cratering rate produced by such variabilities and recalibrate the lunar chronology. We show that it allows to reconcile the crater density measured at mid-latitudes around the Chang'e-5 landing site with the age of the samples collected by this mission. Our updated chronology leads to differences in model ages of up to 30% compared to other chronology systems. The modeled cratering rate variability is then compared with the distribution of lunar craters younger than ∼1 Ma, 1 Ga and 4 Ga. The general trend of the cratering distribution is consistent with the one obtained from dynamical models of NEOs, thus potentially reflecting a nonuniform distribution of orbital parameters of ancient impactor populations, beyond 3.5 Ga ago, i.e., planetary leftovers and cometary bodies. If the nonuniformity of the cratering rate could be tested elsewhere in the Solar System, the recalibrated lunar chronology, corrected from spatial variations of the impact flux and approach conditions of impactors, could be extrapolated on other terrestrial bodies such as Mercury and Mars, at least over the last 3.5 billion years. The modeled cratering rate presented here has strong implications for interpreting results of the Artemis program, aiming to explore the South Pole of our satellite, in particular when it will come to link the radiometric age of the samples collected in this region and the crater density of the sampled units.